ANALISIS BIAYA DAN PRODUKTIVITAS ALAT BERAT PADA KEGIATAN PEMBANGUNAN JALAN BERDASARKAN PERATURAN MENTERI PEKERJAAN UMUM DAN PERUMAHAN RAKYAT (PUPR) NO.28 TAHUN 2016 BIDANG BINA MARGA (Studi Kasus : Pengaspalan Ruas Jalan Tanea – Sanggula, Kecamatan Konda Kabupaten Konawe Selatan) - Bagus Febriono; Baso Mursidi; Aloysius Angela Prima Mangiri (Media Konstruksi : Jurnal Ilmiah Teknik Sipil, 2018)
Infrastructure development in Konawe Selatan District is growing. Development in various sectors, such as roads, is developing in South Konawe District, especially in Andoolo District. The purpose of this study was to determine the productivity and cost of heavy equipment in the widening of the Andoolo City Konawe Selatan Road Section Widening on class B (LPB) aggregate layer work and class A (LPA) aggregate foundation work with reference to the Government Government Regulation Public Works and Public Housing (PUPR) No.28 of 2016. The tools analyzed were wheel loaders, blending equipment, dump trucks, motor graders, vibrator rollers and water tank trucks. The results showed that the Wheel loader had a bucket capacity of 1.50 m3, the equipment rental cost was Rp. 142,378,301.68, Blending equipment capacity of 20 m3 of equipment costs of Rp. 79,860,305.88, Dump truck capacity of 10 tons of tub equipment costs Rp. 273,285,476.55, Motor grader capacity> 100 HP equipment cost of Rp. 14,014,050.75 Vibrator roller with a capacity of 8 T tool cost of Rp. 54,561,495.20, Water tank truck with a capacity of 1000 L for equipment costs of Rp. 23,655,470.76